THE NOTION OF “CONCEPT” IN MODERN LINGUISTICS - Gopporova, Sanobar (Educational Research in Universal Sciences, 2023)
In this article, I will make a brief introduction to a new approach in modern linguistics, the notion of “concept” in modern linguistics, its feature, characteristics, and its development, relationships with other sciences.